2015
DOI: 10.1093/ije/dyv136
|View full text |Cite
|
Sign up to set email alerts
|

New data and an old puzzle: the negative association between schizophrenia and rheumatoid arthritis

Abstract: Our results are consistent with epidemiological observations of a negative relationship between SZ and RA reflecting, at least in part, genetic factors. Results of the month of birth analysis are consistent with pleiotropic effects of genetic variants dependent on environmental context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 69 publications
7
45
1
Order By: Relevance
“…Genetic correlation is a key population parameter that describes the shared genetic architecture of complex traits and diseases [1][2][3] . The genetic correlation is the additive genetic covariance between two traits scaled by the square root of the product of the genetic variance for each trait (i.e., the geometric mean of the trait variances).…”
Section: Main Textmentioning
confidence: 99%
“…Genetic correlation is a key population parameter that describes the shared genetic architecture of complex traits and diseases [1][2][3] . The genetic correlation is the additive genetic covariance between two traits scaled by the square root of the product of the genetic variance for each trait (i.e., the geometric mean of the trait variances).…”
Section: Main Textmentioning
confidence: 99%
“…At~18,000 cases, a much larger number of loci were significant, and, when the number of cases reached~37,000, 108 independent loci were identified. This polygenic liability is now being linked to schizophrenia chronicity (e.g., Meier et al, 2016) and treatment resistance (e.g., Frank et al, 2015) as well as a variety of other psychiatric and medical conditions (e.g., Lee et al, 2015).…”
Section: (D) Genomic Sources Of Heterogeneitymentioning
confidence: 99%
“…In simulations we observed substantial power gain with this weighting scheme. Assuming 1,000 cases and 50 loci, we compared the power of BUHMBOX implemented with and without weighting correlations (equation (12) in Supplementary Information). Across a wide range of π values we observed that the weighting scheme in BUHMBOX dramatically increased power (Figure 2).…”
Section: Weighting Snps By Their Effect Sizes Increases Powermentioning
confidence: 99%
“…Polygenic risk score approaches 3,10,11 build genetic risk scores (GRSs) for one phenotype and test their association with a second phenotype. Mixed-model approaches 5,6,12 can estimate the genetic covariance between two traits on the observed scale. From the genetic covariance one can also calculate the genetic coheritability and genetic correlation 6 .…”
Section: Introductionmentioning
confidence: 99%